Death walks behind you - Hunter, Scott (Great Britain Myrtle Villa Publishing, 2015)
DCI Brendan Moran's last minute break in the West Country proves anything but restful as he becomes embroiled in the mysterious disappearance of an American tourist. Does the village harbour some dark and dreadful secret? The brooding presence of the old manor house and the dysfunctional de Courcy family may hold the answer but Moran soon finds that the residents of Cernham have a rather unorthodox approach to the problem of dealing with outsiders. As Moran is drawn deeper into Cernhams mysterious past a cold-blooded execution in Berkshire plunges deputising DI Charlie Pepper into a maelstrom of murder, double cross and treachery...
111325
Keywords: Police -- England -- Fiction; Missing persons -- Fiction; Dysfunctional families -- Fiction; Executions and executioners -- Fiction; Murder -- Investigation -- Fiction; West Country (England) -- Fiction; Berkshire (England) -- Fiction; Angleterre (Sud-Ouest) -- Romans, nouvelles, etc; England; Detective and mystery fiction; Fiction